Numerical Analysis of Fusion Cross Section of (_^16)O+(_^16)O by Using The Modified Glas-Mosel Formula - Yacobus Yulianto; Zaki Su'ud (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2019)
One of the interesting topics in nuclear reactions is a study about reaction cross section between the interacting nuclei. For calculating fusion cross section, the Glas-Mosel formula has been proven successfully in explaining the experimental results of fusion cross section. In this study, the fusion cross sections of O16+O16 reaction were calculated by using modified Glas-Mosel formula. The energies were set at 10≤?≤40 MeV. The potential of interacting nuclei was approached by using Woods-Saxon potential. In numerical process, the differential equations were solved by using finite different method and optimization process was performed by using Nelder-Mead method. Good agreement between the experimental and this study results has been achieved successfully. Referring those results above, it can be indicated that the modified Glas-Mosel formula has good capability to explain the experimental results of fusion reaction of light nuclei. It can be a useful tool in explaining the experimental results or in predicting fusion cross section of light nuclei.